Differentiated going near the massage of patients the osteochondrosis of lumbar-sacrum sector of spine - Єфіменко [Pavlo Iefimenko], Павло Богуславович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Data are presented about prevalence of lumbar-sacrum osteochondrosis of spine, and his consequences for the health of man. The different mechanisms of his origin, and most widespread methods of rehabilitation, are transferred. The methodical features of the existent generally accepted methods of massotherapy are described. A research purpose was an increase of efficiency of existent methods of massage due to the differentiated going near the state of sick man. Results over of watching are brought the state of fabrics of different areas of body of man at this pathology, that gave certain material for drafting of methods of massage depending on the state of soft fabrics of different areas of body, adjoining to the pathological area from every quarter. The differentiated methods of massage at this pathology and results of her realization a patient are presented in the subsharp period of rehabilitation, on restoration motive mode. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->